A putative multi-sensor hybrid histidine kinase, BarAAc, inhibits the expression of the type III secretion system regulator HrpG in Acidovorax citrulli - Qiao, Pei; Zhao, Mei; Guan, Wei; Walcott, Ron; Ye, Yunfeng; Yang, Yuwen; Zhao, Tingchang (Frontiers in Microbiology, 2022)
Bacterial fruit blotch (BFB), caused by Acidovorax citrulli, severely damages watermelon, melon, and other cucurbit crops worldwide. Although many virulence determinants have been identified in A. citrulli, including swimming motility, twitching motility, biofilm formation, and the type III secretion system (T3SS), research on their regulation is lacking. To study virulence regulation mechanisms, we found a putative histidine kinase BarAAc that may be related to the T3SS regulator HrpG in A. citrulli. We deleted and characterized barAAc (Aave_2063) in A. citrulli Aac5 strain. Compared to the wild-type Aac5, virulence and early colonization of barAAc mutant in host watermelon cotyledons were significantly increased, and induction of hypersensitive response in non-host tobacco was accelerated, while biofilm formation and swimming motility were significantly reduced. In addition, transcriptomic analysis revealed that the expression of many T3SS-related genes was upregulated in the ΔbarAAc deletion mutant when cultured in KB medium. Meanwhile, the ΔbarAAc deletion mutant showed increased accumulation of the T3SS regulator HrpG in KB medium, which may account for the increased deployment of T3SS. This suggests that the putative histidine kinase BarAAc is able to repress the T3SS expression by inhibiting HrpG in the KB medium, which appears to be important for rational energy allocation. In summary, our research provides further understanding of the regulatory network of A. citrulli virulence.